Scaffolding safety assessment in construction sites in Penang - Abu Bakar, Norzalili; Ismail, Mohd Rodzi; Tan , Guat Lin (2008)

(untitled)
This paper discusses about the scaffolding safety in construction sites in Penang. Safety of workers at construction sites is one of the major concerns in construction industry. It is well recognized that the construction industry is one of the most dangerous industries in which to work in. The reasons for these dangers are the hazards faced by the workers in this industry. The equipment of their use on the construction sites are the cause of many of these hazards. One of the equipments with which injuries and death commonly occur among workers is working with scaffolds. Scaffolds play its role by providing passageway, support the structure and as a working platform. They are commonly used for working at heights and where there is the potential risk for workers to fall from height during job done on scaffolding. Falls are the largest cause of accidental death in the construction industry. Therefore, a study has been carried out to investigate and to emphasize on scaffolding hazards and strategies to prevent the hazards. The main objective is to measure the level of safety factor by using scaffolding awareness among employers and construction workers through case study observations in medium sized housing projects and high-rise projects at construction sites in Penang. Questionnaires have been distributed among the employers and unstructured interviews have been conducted with safety officers and officer from the Department of Safety and Health. The results show that scaffolding safety management at the high-rise projects is in compliance with the act and regulation requirements in Malaysia compared to the medium sized housing projects. The study also shows that all employers are well aware of the safety and health regulations in construction sites including scaffolding safety and their responsibilities to reduce fatalities and injuries in the construction industry.